TIPE PERUSAHAAN MEMODERASI UKURAN PERUSAHAAN, PROFITABILITAS, KEPEMILIKAN ASING PADA PENGUNGKAPAN CSR PERUSAHAAN MANUFAKTUR DI BEI - Urmila, Ni Made Diah; Mertha, I Made (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
This study aims to find empirical evidence about the influence of size, profitability, and foreign ownership on the disclosure of CSR, with the types of companies as the moderating variable on manufacturing companies listed in BEI . This study using 34 samples consistent manufacturing companies listed in BEI with a research period of 3 years from 2013 to 2015, bringing the total number of samples during the three years amounted to 102 samples. Factors in this study were tested using MRA. The results of the study identified that profitability significantly positive effect on the disclosure of CSR, while the size and foreign ownership has no significant effect on the disclosure of CSR. Type of company able to moderate the effect of size on the disclosure of CSR, but the type of company is not able to moderate the effect of profitability and foreign ownership on the disclosure of CSR.
Keywords: CSR, company size, profitability, foreign ownership, type of company